Statistical analysis of process parameters in drilling of AL/SICP metal matrix composite - Tosun, Gul (Springer London Ltd, 2011)
This paper presents a statistical analysis of process parameters for surface roughness in drilling of Al/SiCp metal matrix composite. The experimental studies were conducted under varying spindle speed, feed rate, drill type, point angle of drill, and heat treatment. The settings of drilling parameters were determined by using Taguchi experimental design method. The level of importance of the drilling parameters is determined by using analysis of variance. The optimum drilling parameter combination was obtained by using the analysis of signal-to-noise ratio. Through statistical analysis of response variables and signal-to-noise ratios, the determined significant factors were the feed rate and tool type. Confirmation tests verified that the selected optimal combination of process parameter through Taguchi design was able to achieve desired surface roughness. The optimal drilling performance for the surface roughness was obtained at 0.16 mm/rev feed rate, 260 rev/min spindle speed, 130A degrees drill point angle, carbide drill type, and as-received heat treatment settings.
Keywords: Metal matrix composite; Drilling; Surface roughness; Taguchi method; ANOVA